Minimally invasive and hysteroscopic diagnosis and treatment of patients after organ transplantation - Kužel, David; Tóth, Dušan; Cindr, Josef; Hrazdirová, Lucie; Mára, Michal; Viklický, Ondřej (Journal of obstetrics and gynaecology research, 2009)
AIM: To assess the safety of minimally invasive and hysteroscopic diagnosis and treatment of abnormal uterine bleeding and intrauterine abnormalities in patients after organ transplantation. METHODS: After kidney, pancreas, or liver transplantation, patients who presented with menorrhagia, submucosal myoma or thickened endometrium on ultrasound were diagnosed and treated using a hysteroscopic system Versascope, Bipolar Resectoscopic System and intrauterine system ThermaChoice. RESULTS: Twenty patients were included in this study and were aged 37-63 years (average +/- standard deviation: 48.8 +/- 5.86). The follow up was between 3 and 122 months (44.8 +/- 31.91). All hysteroscopic procedures were performed under general anesthesia, using local anesthetics (paracervical block) or short-term i.v. anesthesia, plus antibiotics. The procedures lasted 5 to 15 min (9.4 +/- 2.44). Five patients presented with minimal blood loss (< or =100 mL) and the rest had no blood loss. The hysteroscopic procedures had no adverse effects on the function of transplanted organs and there were no associated postoperative complications. Uterine bleeding was successfully regulated in all patients. CONCLUSION: Minimally invasive procedures and hysteroscopy of organ-transplanted patients provide a safe solution for the treatment of menorrhagia, submucosal myoma and thick endometrium in postmenopausal patients.
Keywords: dospělí; Kidney Transplantation; Humans; následné studie; lidé středního věku; Middle Aged; Organ Transplantation; děložní krvácení; Pancreas Transplantation; Uterine Hemorrhage; transplantace ledvin; Follow-Up Studies; transplantace orgánů; Hysteroscopy; Adult; miniinvazivní chirurgické výkony; Minimally Invasive Surgical Procedures; ženské pohlaví; lidé; hysteroskopie; transplantace slinivky břišní; Female